Human Resource Management at the Tourism, Youth and Sports Office of Jombang District - Saputro, Arnaz Anggoro (Indonesian Journal of Sport Management, 2024)
This study aims to determine the ability of human resource management at the Tourism, Youth and Sports Office of Jombang Regency. This research uses a qualitative descriptive method. The location of this research is the Tourism, Youth and Sports Office of Jombang Regency. This location is very strategic in terms of case studies and problems that occur. The subjects of this research were selected through nonprobability sampling techniques, purposive sampling techniques, or sampling techniques that considered certain aspects. Data collection techniques consist of observation, interviews, and documentation. The results showed that tourism activities have become a service industry in Jombang Regency. The importance of human resources in tourism management is that just one person cannot carry out tourism activities; they must be carried out jointly by a group of people. In this case, the human resource factor becomes a very crucial factor. Human resource management is especially important so that a company, agency, or organization can implement proper management to support quality. The placement of employee positions must also be based on educational background and academic qualifications based on the field of work. The need for more Human Resources capacity human resources with the appropriate educational background can be overcome by providing employee competency development programs, such as training, workshops, or scholarships, to increase academic levels.